2022
DOI: 10.3389/feart.2022.975156
|View full text |Cite
|
Sign up to set email alerts
|

Particle tracking as a vulnerability assessment tool for drinking water production

Abstract: The simulation of concentration values and use of such data for history-matching is often impeded by the computation time of groundwater transport models based on the resolution of the advection-dispersion equation. This is unfortunate because such data are often rich in information and the prediction of concentration values is of great interest for decision making. Particle tracking can be used as an efficient alternative under a series of simplifying assumptions, which are often reasonable at groundwater sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Their approach captured the general trend of vertical distributions of stable isotope values (δ 2 H, δ 2 O, and 4 He), providing indexes of GWV for a 3D, basin-scale, bedrock aquifer. Many other applications have shown that backward particle tracking built upon a calibrated groundwater flow field is a promising process-based approach to assess regional-scale GWV [24][25][26][27][28][29][30][31]. This approach will be used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Their approach captured the general trend of vertical distributions of stable isotope values (δ 2 H, δ 2 O, and 4 He), providing indexes of GWV for a 3D, basin-scale, bedrock aquifer. Many other applications have shown that backward particle tracking built upon a calibrated groundwater flow field is a promising process-based approach to assess regional-scale GWV [24][25][26][27][28][29][30][31]. This approach will be used in this study.…”
Section: Introductionmentioning
confidence: 99%